2007
DOI: 10.1111/j.1467-9450.2007.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of skill level on recall of visually presented patterns of musical notes

Abstract: Expertise effects in music were studied in a new task: the construction of mental representations from separate fragments. Groups of expert musicians and non-musicians were asked to recall note patterns presented visually note by note. Skill-level, musical well-formedness of the note patterns and presentation mode were varied. The musicians recalled note patterns better than the non-musicians, even though the presentation was visual and successive. Furthermore, only musicians' performance was affected by music… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 48 publications
5
29
1
2
Order By: Relevance
“…We compared performance of the two groups on a near-transfer task involving pitch identification and auditory conflict resolution, on several far-transfer tasks involving visuospatial memory span and cognitive control processes (conflict resolution, resistance to distraction, and response inhibition), and on a composite measure of cognitive control. Research with young and middle-aged amateur and professional musicians has shown enhancement on far-transfer tasks involving visuospatial function and cognitive control [12], [19], [40][41]. On the basis of enhanced auditory processing and working memory in older amateur musicians [33][34], we expected late middle-aged to older professional musicians to perform better than non-musicians on the near-transfer task.…”
Section: Introductionmentioning
confidence: 87%
“…We compared performance of the two groups on a near-transfer task involving pitch identification and auditory conflict resolution, on several far-transfer tasks involving visuospatial memory span and cognitive control processes (conflict resolution, resistance to distraction, and response inhibition), and on a composite measure of cognitive control. Research with young and middle-aged amateur and professional musicians has shown enhancement on far-transfer tasks involving visuospatial function and cognitive control [12], [19], [40][41]. On the basis of enhanced auditory processing and working memory in older amateur musicians [33][34], we expected late middle-aged to older professional musicians to perform better than non-musicians on the near-transfer task.…”
Section: Introductionmentioning
confidence: 87%
“…Expertise increases the ability to recognize and recall a meaningful pattern (Barfield, 1997;Garland & Barry, 1991;Gobet & Simon, 1996;Halpern & Bower, 1982;Kalakoski, 2007;Kawamura, Suzuki, & Morikawa, 2007). Chess experts, for example, can quickly recognize and later recall the number of chess pieces by grouping individual items into meaningful "chunks" (Gobet, 1998;Gobet & Clarkson, 2004;McGregor & Howes, 2002).…”
Section: Effects Of Expertisementioning
confidence: 99%
“…The increased neural activity is explained by stronger acoustic encoding of musical sounds and also by the representation of stimuli in terms of multiple codes that can be exploited automatically [7]. For example, musicians recall visual patterns of successive musical notes better than non-musicians, probably because of musicians' knowledge of sound-labels [8]. However, evidence also indicates that musicians benefit from enhanced domain-general cognitive processes, including enhanced mathematical, verbal, and non-verbal skills [9], [10], [11], and non-musical enhancement of working memory in musicians has repeatedly been demonstrated.…”
Section: Introductionmentioning
confidence: 99%